How does sowing density affect physiology, yield, and quality of red cabbage microgreens? - Cecílio Filho, Arthur Bernardes [UNESP]; Pindobeira, Wellington Missiano [UNESP]; Alves, Thatiane Nepomuceno [UNESP]; Ribera, Laura Matos [UNESP]; Yañez Medelo, María José [UNESP] (FapUNIFESP (SciELO), 2025)
Red cabbage microgreens, with high nutraceutical value and peculiar sensory characteristics, has been one of the most studied microgreens for cultivation in plant factories, especially under red and blue light irradiance. However, under white light, it is necessary to know the effect of sowing density on their physiology, yield, and quality, which is the objective of the present study. Five sowing densities (60, 120, 180, 240, and 300 g·m–2) were evaluated in an indoor environment under photosynthetic photon flux density of 250 μmol·m–2·s–1 of white light + 20 μmol·m–2·s–1 of red light, and photoperiod of 20 h. Increase in sowing density caused greater competition among seedlings, which increased hypocotyl length and reduced cotyledon area and shoot dry mass of the microgreens. However, the perceived decreases in the individual plant mass were offset by an increase in the number of plants, which resulted in higher yields as sowing density increased. Efficiency of photosystem II, initial fluorescence, and maximum fluorescence were not influenced by sowing density. As for the quality of microgreens, increasing the sowing density resulted in an effect contrary to that observed for yield and reduced contents of calcium, iron, pigments, and ascorbic acid.
Keywords: Brassica oleracea var. capitata f. rubra; indoor farm; plant factory; superfood; urban agriculture